Do Students Read Teacher Evaluation Surveys when Participation Incentives are Applied? An Empirical Approach - Luis Matosas-López; Alberto Romero-Ania; Elena Cuevas-Molano (Universidad Autónoma de Madrid, 2019)
The purpose of this study is to reveal the extent to which university read teacher evaluation surveys when participation incentives are applied. Researchers carry out a quantitative study, in which an experimental methodology with two groups is adopted. The first group performs the assessment of the teacher in a scenario free of incentives; the second completes the survey in an incentivized participation scenario. In addition, the research considers two types of questionnaires: on the one hand, Likert scales, on the other hand, scales with behavioral episodes or bars. The research uses descriptive analysis, Student´s t-test, and analysis of correlations through the Pearson correlation coefficient. The findings reveal differences in the investment of time when participation incentives are applied. It can be concluded that the instruments with Likert scales do not favor the correct reading and completion of surveys when the evaluation introduces rewards. However, this situation can be improved using bars questionnaires. The present study sheds light on a problem practically ignored by previous literature, but also introduces alternatives for improvement.